Emergence of a resistance anomaly by Cu-doping in TaSe3. (14th September 2017) - Nomura, A.; Yamaya, K.; Takayanagi, S.; Ichimura, K.; Matsuura, T.; Tanda, S.
Abstract: We have synthesized single crystals doped with Cu atoms in TaSe3 which exhibits no Charge Density Wave (CDW) transition, and measured precisely the temperature dependence of the resistance. We discover an anomalous sharp dip in the temperature derivative of the resistance at about 91 K in Cu-doped TaSe3, which is never observed in pure TaSe3 . The dip suggests that there is a phase transition with a relative increase in resistance. In addition, the dip is " γ " shaped. We reveal that the same " γ "-shaped dip in d R /d T is commonly observed at the CDW transition temperature in many CDW conductors, which is a universal consequence resulting from the opening and growth of a CDW gap on a Fermi surface. Furthermore, the result of the single-crystal X-ray diffraction (XRD) analysis implies that Cu-doping increases the lattice parameter of the a -axis and c -axis and decreases that of the b -axis, leading to an improvement in the nesting condition. Based on the " γ "-shaped dip and the result of the single-crystal XRD analysis, we conclude that a CDW emerges by Cu-doping in TaSe3 .